Biomass resources for energy in North-Eastern Brazil - Badr, Ossama; Filho, Pedro Anselmo (Elsevier Science B.V., Amsterdam., 2004)
Due to the high dependency on hydroelectric power generation, Brazil faced a power shortage in 2001. In order to remedy the situation and avoid more severe power crises in the future, the Brazilian Government launched incentive programmes to encourage thermal and renewable power generation. The Programme of Incentives to Alternative Sources (PROINFA) is mainly devoted to the utilisation of biomass. The success of PROINFA depends on the availability of reliable studies for assessing existing biomass resources and the viability of their utilisation for power generation. In this study, energy potentials of the main biomass resources in the north-eastern region of Brazil have been assessed. The economy of the north-eastern region of Brazil is heavily dependent on its sugar industry. Biomass available from sugarcane cultivation and processing represents an annual regional energy resource of 40.5 TWh at an average cost of US$ 0.005/ kWh. Bamboo, cultivated as a dedicated energy crop, has the second largest annual energy potential of 30.8 TWh at an average cost of US$ 0.009/kWh. Municipal solid waste, generated in the region, has an annual energy potential of about 16.7 TWh.